The cost–utility of lumbar disc herniation surgery - Hansson, Elisabeth (Springer-Verlag, 2006)
The cost and utility of surgery for a herniated lumbar disc has not been determined simultaneously in a single cohort. The aim of this study is to perform a cost–utility analysis of surgical and nonsurgical treatment of patients with lumbar disc herniation. Ninety-two individuals in a cohort of 1,146 Swedish subjects underwent lumbar disc herniation surgery during a 2-year study. Each person operated on was individually matched with one treated conservatively. The effects and costs of the treatments were determined individually. By estimating quality of life before and after the treatment, the number of quality adjusted life years (QALY) gained with and without surgery was calculated. The medical costs were much higher for surgical treatment; however, the total costs, including disability costs, were lower among those treated surgically. Surgery meant fewer recurrences and less permanent disability benefits. The gain in QALY was ten times higher among those operated. Lower total costs and better utility resulted in a better cost utility for surgical treatment. Surgery for lumbar disc herniation was cost-effective. The total costs for surgery were lower due to lower recurrence rates and fewer disability benefits, and surgery improved quality of life much more than nonsurgical treatments.